Women solders and citizenship in Israel - Lomsky-Feder, Edna, author.
1 online resource
Keywords: "Women Solders and Citizenship in Israel: Gendered Encounters with the State is an important and rigorous study exploring the varied and shifting meanings that Israeli women ascribe to their military service. By analysing life stories and testimonies of over 120 women the text examines: How do women's gendered ethno-class positions shape their experiences of military service? How does the gendering of military roles shape women's gender awareness and their perceptions of citizenship? And how do women's specific positions in the military shape their awareness of, and reaction to, the state's inherent violence? This study should appeal to scholars and students of sociology, political science, gender studies, military sociology, political anthropology, social policy, Israel studies, and Middle East studies"--